Latino homicide: immigration, violence, and community - Martínez, Ramiro (Criminal justice series, 2015)
"Latino Homicide is the first empirically based, but readable book for courses to counter the conventional wisdom that immigrant populations only contribute crime to their communities. For this second edition, Martinez further emphasizes his argument with updated data and the addition of a new city, San Antonio. With fascinating case studies from police reports and actual cases from six varied cities, Latino homicide rates are revealed to be markedly lower than one would expect, given the economic deprivation of these urban areas. Far from dangerous or criminal, these communities often have exceptionally strong social networks precisely because of their shared immigrant experiences. Martinez skillfully refutes negative stereotypes in a coherent and critically rigorous analysis of the issues"--